2020
DOI: 10.1515/pp-2020-0113
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR spectroscopy metabonomics of reactive, ovarian carcinoma and hepatocellular carcinoma ascites

Abstract: BackgroundMetabolomic profiling of human malignant effusion remain a field poorly investigated. Proton nuclear magnetic resonance (1H-NMR) spectroscopy is a rapid relatively low cost technique, and effusion is an optimal biospecimen suitable for metabonomic investigations. With this study we addressed metabolomic profiling of malignant ascitic effusion (mAE) from patients with high grade serous ovarian carcinoma (HGSOC), Hepatocellular carcinoma (HCC), and benign AEs (bAEs) from patients with reactive peritoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Compared with urine and plasma, ascites is highly selective in ltering and concentrating plasma metabolites through the serosa. Therefore, ascites may become an ideal uid for the study of metabonomics for the discovery of biomarkers [18,19]. Recurrent ascites and rapid resistance to platinum therapy are common in advanced ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with urine and plasma, ascites is highly selective in ltering and concentrating plasma metabolites through the serosa. Therefore, ascites may become an ideal uid for the study of metabonomics for the discovery of biomarkers [18,19]. Recurrent ascites and rapid resistance to platinum therapy are common in advanced ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This same technique was employed to investigate ascites associated with both reactive ovarian carcinoma and hepatocellular carcinoma (HCC). The ovarian carcinoma ascites was enriched in alanine, phenylalanine and lipids and depleted in glutamine [16]. A study of serum from cirrhotic ascites patients and healthy controls was reported, in which 12 amino acids and 8 conjugated bile acids were significantly increased in the ascites patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to distinguish cirrhotic, malignant, cardiac and inflammatory origins of ascites go back to the 1950s with paper chromatography used to measure proteins such as albumin, α1, α2 and È-globulin fractions [4], followed by radial immunodiffusion introduced in 1965. A total of Molecules 2022, 27, 3935 2 of 16 23 plasma proteins in ascites were determined using this methodology [5]. Lipoproteins [6] and bile acids [7] in ascites have also been determined in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid chromatography along with mass spectrometry (LC-MS), nuclear magnetic resonance (NMR), and gas chromatography MS (GC-MS) as some techniques is implemented to identify and quantify metabolites [ 13 ]. Metabolites such as plasma, urine, milk, saliva, amniotic fluid, tissue extracts, cerebrospinal fluid, bile, fecal extracts and semen can be detected by the above techniques [ 14 21 ].…”
Section: Introductionmentioning
confidence: 99%